The Successful Covid-19 Vaccine Rollout in Chile: Factors and Challenges - Maddaleno-Herrera, M; Villalobos-Dintrans, P; Castillo-Corral, C (Elsevier Ltd, 2021)
As the COVID-19 pandemic continues causing problems around the world, Chile is facing a new episode of increasing cases and deaths. However, at the same time, the country has succeeded in providing vaccines for an important part of its population over a short period. What are the factors behind this successful process? What are the challenges faced by the country today? This article explores potential explanations for the “Chilean paradigm”, regarding the COVID-19 vaccine rollout. Borrowing from implementation science frameworks, the analysis proposed an alternative explanation—based on multiple actors, approaches, and history—as opposed to one in which the outcome is due mainly to the government s performance. The rapid and extensive coverage of vaccination can be explained by the role played by the government and the academia in securing vaccines through a pragmatic approach; the capacity built at local level, as well as the coordination between the health system and local authorities; and favorable vaccine culture, developed through the implementation of the National Immunization Program. Short and long-term elements (such as investment in infrastructure and relationships between stakeholders, and actions carried out during the pandemic), as well as contextual factors (such as the political and socioeconomic context), provide a more complex story to explain the observed outcomes. While other countries could try to follow the Chilean example, the article shows that short-term actions are necessary but might not be sufficient to achieve results. At a global level, the situation calls for rethinking how countries will face these global challenges, including issues such as international cooperation and global health governance. © 2021 The Authors